PHYTOCHEMICAL SCREENING AND BIOLOGICAL EFFECTS OF LAURUS NOBILIS (LAURACEAE) ESSENTIAL OIL AGAINST MOSQUITO LARVAE, CULEX PIPIENS (LINNEAUS, 1758) (DIPTERA: CULICIDAE) SPECIES - AISSAOUI, L; BOUAZIZ, A; BOUDJELIDA, H; NAZLI, A (My University, 2022)
The present study aimed to determine the phytochemical compounds and to evaluate the activities of the essential oil (EO) of Laurus nobilis against mosquito larvae, Culex pipiens. The EO was extracted by hydro-distillation from L. nobilis leaves and subsequently, their chemical profile was identified by gas chromatography coupled with mass spectrometry (GC-MS) method. 39 compounds, representing 99.98% of the crude oil were identified; namely 1.8-cineole (22.42%), isolongifolene (10.22%), 3-carene (7.74%), Alpha-zingiberene (6.69%), Eremophilene (4.87%), Aristola-1 (10), 8- diene (3.09%) icyclo, sabinene (4.13%), α-pinene (1.94%) and Beta-caryophyllene (0.36%). Overall, 21 of these components, out of 39, were over 1%. The L. nobilis EO toxicity was tested at different concentrations, ranging between 5 and 35 µl/l, against third and fourth-instar of Cx. pipiens larvae. Mortality was recorded for both stages and their lethal concentrations (LC50 and LC90) were estimated at 3.74 µl/l and 14.47 µl/l for the third-instar larvae and 18 µl/l and 39.08 µl/l for the fourth-instar larvae, respectively. The bioassay results showed a larvicidal effect with a concentration response– relationship. Furthermore, the compound effects, applied at LC50 and LC90 against the fourth-instars larvae showed an increase in the development duration and a disturbance in reproduction. The investigation confirmed the toxicological effects of L. nobilis EO against mosquito larvae; consequently, it could be considered as a potent source for producing natural larvicidal agents and bioinsecticides for pest an insect vector control